2009
DOI: 10.1901/jaba.2009.42-369
|View full text |Cite
|
Sign up to set email alerts
|

Interteaching: The Effects of Quality Points on Exam Scores

Abstract: Although previous studies have found interteaching to be an effective alternative to traditional methods of instruction, few studies have examined which of its components contribute to its effectiveness. In the current study, we examined whether manipulating quality points had an effect on our students' exam scores. In two sections of an undergraduate general psychology course, we used interteaching but alternated between quality points and no quality points several times throughout the semester; we also count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 10 publications
0
46
0
Order By: Relevance
“…Thus, it is likely that the students completed the homework assignments during no-points weeks, but with no contingency in place for their submission, the students did not expend the effort to prepare their assignments in a format suitable for submission. Guring (2003) reported that undergraduate students rated homework questions as among the most helpful study tools (see also Saville & Zinn, 2009). Unlike the undergraduate students in Ryan and Hemmes, the graduate student participants in this study had lengthy histories during which certain study skills had been selected and refined.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, it is likely that the students completed the homework assignments during no-points weeks, but with no contingency in place for their submission, the students did not expend the effort to prepare their assignments in a format suitable for submission. Guring (2003) reported that undergraduate students rated homework questions as among the most helpful study tools (see also Saville & Zinn, 2009). Unlike the undergraduate students in Ryan and Hemmes, the graduate student participants in this study had lengthy histories during which certain study skills had been selected and refined.…”
Section: Resultsmentioning
confidence: 97%
“…Saville and Zinn (2009) examined the quality-points component of interteaching by comparing the exam scores of students in two sections of an introductory psychology course. Saville and Zinn alternated between interteaching with quality points and interteaching without quality points, counterbalanced across sections, and awarded quality points by comparing the essay answers of students who completed the pair discussions together (see Boyce & Hineline, 2002).…”
Section: Is Interteaching Effective?mentioning
confidence: 99%
“…Sidman also discussed the importance of systematic replication, in which a researcher examines whether a phenomenon occurs under conditions that differ from those prevailing in the original experiment. Although we have used interteaching in a number of our undergraduate and graduate courses, the researchers who have thus far published their findings on interteaching have used relatively small convenience samples consisting of introductory psychology students (see Saville et al, 2005;Saville & Zinn, 2009), students in undergraduate research methods courses (Saville et al, 2006, Study 2), or students in a graduate-level special education course (Saville et al, 2006, Study 1). It would therefore be interesting to examine whether interteaching produces similar results in other types of psychology courses-large, survey-level courses; smaller, capstone-level courses; graduate-level seminars; and even distance-learning courses.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final component is the frequent exam as the primary measure of learning in the interteaching classroom (for a more detailed description of interteaching, see Boyce & Hineline, 2002;Saville, Lambert, & Robertson, 2011). Interteaching component analyses research has focused on the inclusion of prep guides (Saville, Zinn, & Serdikoff, 2008), reinforcing properties of quality points (Saville & Zinn, 2009), and the types of prep guides used, specifically instructor-created prep guides or prep guides where students generate their own questions (Cannella-Malone, Axe, & Parker, 2009). These studies have begun to uncover the underlying mechanisms making interteaching effective (Saville et al, 2011).…”
Section: Introductionmentioning
confidence: 99%